Computational approaches to elucidate the action mechanism of zerumbone towards beta catenin - Fatima, Ayesha (2017)
Cancer is the fourth leading cause of all deaths in Malaysia with 13.56% deaths due to cancer in 2014. Wnt-β-catenin signaling pathway plays a significant role in cell proliferation and migration. Due to this, it has been implicated in several human cancers. β-catenin is the key protein of the Wnt-β-catenin signaling pathway that is involved in maintaining the cell-cell adhesion by binding to the e-cadherin and β-catenin and cell proliferation by complexing with transcription factor, Lymphoid Enhancing Factor 1 (LEF1)/T-cell Factor 4 (TCF4), in the nucleus. Zerumbone is a sesquiterpine with known anticancer properties. The action of zerumbone towards β-catenin was investigated using several computational techniques. Docking studies was done with CDOCKER. Zerumbone was docked to β-catenin with and without TCF4 to represent structures of β-catenin in the nucleus and in the cytoplasm, respectively. Binding energy of -60.58 kcal/mole was obtained when zerumbone was docked to the β-catenin without TCF4. Trp338, Arg342, Lys345, Arg376, Asn380 and Trp383 formed the binding site residues. When zerumbone was docked to the β-catenin-TCF4 complex, it interacted with residues of both β-catenin and TCF4. The binding energy of the β-catenin-TCF4-zerumbone complex was -80.8 kcal/mol and the binding pocket residues were Lys345, Trp383, Arg386, Asn387, Asn415 of β-catenin and residues Glu24, Gly25, Gln27, Glu28 of TCF4. The results indicated that zerumbone was bound more strongly to the β-catenin-TCF4 complex than β-catenin without TCF4.The stability of the β-catenin-zerumbone and β-catenin-TCF4-zerumbone complexes was futher investigated by molecular dynamics simulation technique implemented in AMBER12 for 50ns. The β-catenin-zerumbone complex with RMSD values between 3- 6Å indicated an effort in forming a stable complex. The β-catenin-TCF4-zerumbone complex, on the other hand, with RMSD values between 4-5Å demonstrated the formation of a stable complex. The MMPBSA/GBSA methods used for calculating the average free binding energy of the last 5ns simulation the complexes showed that the PBTOTAL and GBTOTAL values of the β-catenin-zerumbone complex were -7.94 kcal/mol and -7.54 kcal/mol, respectively. The same values for the β-catenin-TCF4- zerumbone complex were -15.23 kcal/mol and -14.88 kcal/mol, respectively. The hybrid QM/MM molecular dynamics provided deeper insight into the binding site interactions of the β-catenin-TCF4-zerumbone complex. The binding site of zerumbone with the key residues Lys345, Trp383, Arg386 of β-catenin and Gln27 and Glu28 of TCF4 was treated by QM PM6 semi-empirical theory, while the remaining protein was treated with MM theory using AMBER12. The 5ns simulation data showed that the RMSD of the QM treated region was between 2-2.5 Å. The free binding energy of the QM treated region was -15.68 kcal/mol illustrated that zerumbone was tightly bound to the complex. The structural data indicated that the ring structure of zerumbone formed π-π interactions with the aromatic rings of Trp383 of β-catenin while Arg386 also from β-catenin formed hydrogen bond with the carbonyl oxygen of zerumbone lending stability to the binding of zerumbone to the complex. Steered molecular dynamics method in GROMACS 5.0.4 software was used to estimate the strength of interaction of the β-catenin-TCF4 complex in the presence of zerumbone. The results indicated that the β-catenin-TCF4 complex interaction was 1963.1 kJ/mol/nm which was considerably less when compared to 2221.9 kJ/mol/nm when zerumbone. In-vitro experiments conducted on HepG2 cell lines demonstrated that the nuclear: cytoplasmic ratio of β- catenin decreased significantly at 8μg/mL indicating decreased translocation of β- catenin into the nucleus. In conclusion from our investigation, zerumbone targets β-catenin in the cytoplasm as well as in the nucleus when it is bound to the transcription cofactor, TCF4.